Analysis of the Influence of Students' Attitudes on High School Students' Learning Motivation - M. Al Amin; Siti Hedon Sheikh Abdullah; Hagar El-Mahalawy (Schrödinger: Journal of Physics Education, 2023)
Purpose of the study: The purpose of this study is to find out how the influence of attitudes on motivation to learn about the problems that occur in learning physics. Methodology: The method used in this study is a quantitative method using survey assessment stages. The sampling technique used simple random sampling with a total sample of 72 high school students. The data collection technique uses a questionnaire on learning motivation and student attitudes. Data analysis used a simple linear regression hypothesis test assisted by SPSS software. Main Findings: The results of the research and testing of the hypothesis can be concluded that there is a significant positive influence on students' learning attitudes towards physics learning motivation. Each increase in one unit of learning attitude will increase learning motivation by 0.91 units significantly. Novelty/Originality of this study: The novelty of this research is the discovery of a positive influence of students' learning attitudes on their physics learning motivation. Where every increase of one unit of students' learning attitudes will increase 0.91 students' motivation to learn physics.